Mitochondria-targeted organic sonodynamic therapy agents: concept, benefits, and future directions - Hwang, Eunbin; Yun, Minjae; Jung, Hyo Sung (Frontiers in Chemistry, 2023)
Sonodynamic therapy (SDT) is an emerging and potentially less invasive therapeutic approach for cancer that employs ultrasound (US)-sensitive agents combined with US irradiation to generate cytotoxic reactive oxygen species (ROS) in deep tumor regions. Among various cellular organelles, the mitochondria are particularly susceptible to ROS, making them an attractive target for SDT. Organic-based SDT agents with mitochondria-targeting affinity have gained considerable interest as potential alternatives to conventional SDT agents, offering significant advantages in the field of SDT. However, to date, a comprehensive review focusing on mitochondria-targeted SDT agents has not yet been published. In this review, we provide an overview of the general concept, importance, benefits, and limitations of mitochondria-targeted organic SDT agents in comparison to conventional SDT methods. Finally, we discuss the current challenges and future directions for the design and development of efficient SDT agents. By addressing these issues, we aim to stimulate further research and advancements in the field of mitochondria-targeted SDT, ultimately facilitating the translation of these agents into clinical applications.